PELAKSANAAN MENTORSHIP OLEH PERAWAT PENYAKIT JANTUNG TERPADU DI RSUP H. ADAM MALIK MEDAN - Eva Kartika Hasibuan; Nurmaini Nurmaini; Sri Eka Wahyuni (Jurnal Online Keperawatan Indonesia, 2018)
Mentoring is mutually beneficial between someone who has the advantage in experience and someone who does not. Informal mentoring is done spontaneously with the span of time according to the mentee’s need; it does not need preparation (impromptu) for mentoring process, it occurs voluntarily, and it is established according to mutual confidence building between a mentor and a mentee. The objective of the research was to dig up nurses’ experience in implementing mentorship in RSUP H. Adam Malik, Medan. The research was qualitative with descriptive phenomenological method. The data were gathered by conducting in-depth interviews and field recording. The samples were 9 nurses as the respondents, taken by using purposive sampling technique with inclusive criteria: nurses with the rank of PK 2 and PK 3 in career, ward heads, and the team heads in PJT (Integrated Heart Disease) Room. The result of the interviews was analyzed by using NVivo Version 11.0 (trial) software program. The result of the research showed that there were 2 themes, 4 sub-themes, and 10 categories. The themes were getting hope in implementing mentorship, and getting obstacles in implementing mentorship. It is recommended the hospital management make specific standard and format and specific schedule and time so that there will be uniformity in implementing mentorship. It is also recommended that the next researchers dig up their researches profoundly so that there will more themes with more respondents in order that the result of the research will be better